School Committee Participation in Improving the Quality of Education - Jaelani, Jaelani; Hanif, Muh. (Jawda: Journal of Islamic Education Management, 2025)
School Committees in Indonesia hold a strategic mandate to improve the quality of education; however, their concrete contributions in rural elementary schools remain insufficiently explored, particularly regarding the governance-practice gap. This study employed a qualitative case study approach at SD Negeri 01 Badak, utilizing participatory observation, in-depth interviews (with the principal, teachers, and the committee chair), and document analysis. The committee was actively involved in fundraising (e.g., graduation events), providing physical facilities (e.g., a prayer room and student chairs), and planning school programs. However, the oversight of program implementation was weak due to members’ limited understanding of their strategic roles and time constraints, which created disparities between resources and pedagogical needs. Optimizing school-community partnerships requires targeted capacity-building efforts and structured accountability mechanisms to bridge the gap between normative and practical aspects. This study reveals governance disparities within rural School Committees. It contributes to participatory management theory by demonstrating how local socio-cultural constraints, such as parental time poverty, shape decentralization in resource-limited areas.